Morphometric Evaluation of Interrenal Gland and Kidney Macrophages Aggregates in Normal Healthy Rainbow Trout (Oncorhynchus mykiss) and after Bacterial Challenge with Yersinia ruckeri. (24th February 2014) - Gregori, Michela; Miragliotta, Vincenzo; Leotta, Roberto; Cecchini, Stefano; Prearo, Marino; Abramo, Francesca
Abstract : Macrophage aggregates (MA) occur in various organs of fish as discrete aggregations of pigmented macrophages. The study presented herein investigates the quantitative modifications from normal anatomical condition, of interrenal gland (IG) and kidney MA in six treatment groups of adult rainbow trout submitted to either specific or aspecific immune stimulation and subsequently challenged with Yersinia ruckeri . Routinely stained tissue sections from both IG and kidney were analysed. The percentage of tissues occupied by MA and the MA density (number/mm 2 ) were calculated on at least 10 randomly selected nonoverlapping fields taken from each tissue section. MA morphometric findings from challenged fish were compared to those from a control group. Results showed that fish from control group displayed a statistically significant (P < 0.05 ) higher percentage of tissue occupied by MA and MA density. Among different treatment groups, anti- Yersinia ruckeri immunized fish, which did not show clinical signs of disease after bacterial challenge, displayed higher values of morphometric parameters compared with symptomatic fish from other groups. Our study demonstrates that the quantification of the area occupied by MA might be an efficient parameter to evaluate the general condition of a salmonid population since it positively correlates with the health status and negatively with stress factor such as the acute bacterial infection.